Animal Welfare in World Religion: Teaching and Practice - D'Silva, Joyce (Taylor & Francis Group, 2023)
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Acknowledgements -- Introduction -- 1 Judaism: Teaching and Practice Regarding Humanity's Relationship with Animals -- 2 Christianity: Teaching and Practice Regarding Humanity's Relationship with Animals -- 3 Islam: Teaching and Practice Regarding Humanity's Relationship with Animals -- 4 Hinduism: Teaching and Practice Regarding Humanity's Relationship with Animals -- 5 Buddhism: Teaching and Practice Regarding Humanity's Relationship with Animals -- 6 Beyond the Major World Religions: Teaching and Practice Regarding Humanity's Relationship with Animals -- Conclusion -- Glossary -- Index.